Application of Blockchain for Tracking Government Funds: Case Studies on Distribution of Regional Transfer Funds - Hakim, Lutfi; Aji, Rizal Fathoni (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Tracking of Regional Transfer Funds from the Central Government to Regional Governments cannot be carried out optimally which causes the potential for fraud. The tracking in question is related to how long the funds have been sitting in the regional bank before being distributed, when should the funds be distributed, and whether the funds have been used to pay for a predetermined project. This research is a qualitative research through literature studies, observations and interviews which aims to analyze whether blockchain can be the right solution for the problem of tracking regional transfer funds. Based on an analysis using the Enterprise Blockchain Design Framework (EDBF), blockchain can be an alternative solution to this problem, especially if it is built with the characteristics of a Private/Consortium Permitted Blockchain using Hyperledger Fabric. There are five participants in the proposed design starting from government agencies and banking. The results of this design were verified by system developers at the Ministry of Finance, the results of this technology have the potential to be applied and overcome the problem of tracking regional transfer funds.